Molar incisor hypomineralisation: Possible aetiological factors in children from urban and rural areas - Souza, J. F. [UNESP]; Costa-Silva, C. M.; Jeremias, F. [UNESP]; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Zuanon, Angela Cristina Cilense [UNESP]; Cordeiro, Rita de Cássia Loiola [UNESP] (Springer Nature, 2012)
Aim: To analyse factors potentially associated with molar incisor hypomineralisation (MIH) development. METHODS: A population-based study was carried out with 903 children aged from 6-12 years old, born and residing in rural and urban areas of the town of Botelhos, State of Minas Gerais, Brazil. Their mothers completed a structured medical history questionnaire, from pregnancy to the child's 3rd year of life. Two examiners evaluated children for MIH according to criteria suggested by the European Academy of Paediatric Dentistry. Descriptive analyses of the data and odds ratios (OR) with 95% test-based confidence intervals (CI) were estimated. Chisquare test was used to evaluate the differences between groups. RESULTS: The prevalence of MIH in children from rural area (RA) was significantly higher than those from the urban area (UA) (24.9% versus 17.8%, p= 0.01). In urban children, neither significant associations with MIH nor medical problems were found. In rural children, however, MIH was significantly more common among those whose mothers had experienced medical problems during pregnancy (OR=2.11; 1.01-4.37 CI 95%; p=0.04), who had throat infections (OR=2.93; 1.47-5.87 CI 95%; p=0.01), who had high fever (OR=1.91; 1.07-3.39 CI 95%; p=0.02), and who had used amoxicillin associated with other antibiotics (OR=1.92; 1.02-3.62 CI 95%; p=0.04) during the first 3 years of life. CONCLUSION: This study suggests a link between MIH and health problems during pregnancy, as well as environmental factors.
Keywords: Aetiology; Epidemiology; Molar incisor hypomineralisation; amoxicillin; antiinfective agent; anamnesis; Brazil; child; enamel hypoplasia; female; fever; health; health survey; human; male; pharyngitis; pregnancy; pregnancy complication; prevalence; risk factor; statistics; Amoxicillin; Anti-Bacterial Agents; Child; Dental Enamel Hypoplasia; Female; Fever; Humans; Male; Medical History Taking; Pharyngitis; Population Surveillance; Pregnancy; Pregnancy Complications; Prevalence; Risk Factors; Rural Health; Urban Health